Posturographic analysis of induced emotion: a scoping review - Hakimi, Adrien; Nourry, Adrien; Mouras, Harold; Lelard, Thierry (Frontiers in Human Neuroscience, 2025)
Posturography is a useful technique that allows to explore postural control, a complex motor skill enabling body orientation and stability. Analyzing postural control is one way to assess body responses to various emotional stimuli. By examining the displacement of the center of pressure, it is possible to investigate postural adjustments of individuals confronted with emotional stimuli. This scoping review focuses on the use of this methodology over the last decade. Forty-eight studies were included, covering a wide range of emotional themes studied around the world. Posturography appears to be a frequently used tool for assessing responses to emotional content. There is a high variability in the methods used in these studies and sometimes a lack of information regarding methodological concerns. This review provides methodological recommendations to standardize reporting in posturographic studies of emotions. It is likely that more and more topics will be studied in the coming years.